Culture and Extremism. (9th September 2013) - Gelfand, Michele J.; LaFree, Gary; Fahey, Susan; Feinberg, Emily
Abstract : Much research in the last several decades has examined the social, political, and economic factors that predict terrorism, yet to date, there has been little attention to cultural factors and their relationship to terrorism. We present findings from the Global Terrorism Database showing how numerous cultural dimensions identified in the cultural psychology literature relate to over 80, 000 terrorist attacks that occurred between 1970 and 2007. Controlling for economic and religious variables, our results suggest that fatalistic beliefs, rigid gender roles, and greater tightness are related to a greater number of terrorist attacks or fatalities. While fatalism and low gender egalitarianism were related to the overall number of terrorist incidents and fatalities, cultural tightness was related the overall lethality of events, i.e., fatalities per incident. We discuss theoretical and practical implications of our findings.